A pilot study investigating anterior segment optical coherence tomography angiography as a non-invasive tool in evaluating corneal vascularisation - Ong, Hon Shing (2021)
The current assessment of corneal vascularisation (CV) relies on slit-lamp examination, which may be subjective. Dye-based angiographies, like indocyanine green angiography (ICGA), allows for good visualisation of anterior segment blood vessels. However, ICGA is invasive and can be associated with systemic adverse effects. Anterior segment optical coherence tomography angiography (AS-OCTA) is a non-invasive tool that has been shown to successfully delineate CV. However, there are no previous studies that have reported if AS-OCTA can determine CV stage and activity. We used an established CV model in rabbits to examine serial AS-OCTA scans of CV development and regression following treatment with anti-vascular endothelial growth factor. We compared AS-OCTA derived vascular measurements to that of ICGA determined vessel leakage and CV staging. Our results showed that AS-OCTA vessel densities and vessel branch area significantly correlated with the severity of CV based on ICGA (all p ≤ 0.05). We also found that AS-OCTA vessel densities correlated with ICGA vessel leakage time, following an inverse linear relationship (r2 = - 0.726, p < 0.01). Changes in aqueous levels of CXCL-12 and PIGF cytokines significantly correlated with AS-OCTA vessel densities (r2 = 0.736 and r2 = 0.731 respectively, all p < 0.05). In summary, we found that AS-OCTA derived vessel parameters may be useful for assessing CV severity, while vessel density correlates with CV activity and leakage. Thus, our pilot animal model study suggests that AS-OCTA may be a useful non-invasive imaging tool to provide objective assessment of CV to examine progression or response in treatment, which requires confirmation in clinical studies.